Iterations and translations. The role of painting as a discursive tool for collaborative colour design practice in architecture - McLachlan, Fiona (AREA - Agenda de Reflexión en Arquitectura, Diseño y Urbanismo, 2025)
Colour design for architecture is an iterative process of research, experimentation, testing and adjustment. At every stage individual judgement plays its part in refining and resolving a design, while different opinions will need to be navigated through discussion. The paper will outline the methods, techniques and procedures involved in the evolution of a colour design for the renovation of two brutalist housing blocks from the 1960s in Edinburgh, Scotland. The research methodology for the project is rooted in the experiential, analogue methods developed by Haus der Farbe in Zurich, Switzerland. In this case however, abstract paintings and collage are used in parallel with digital tools to facilitate the development of a colour design within the conventions of contemporary architectural practice. The focus was to develop a colour strategy that would guide the decisions through subsequent iterations and translations that are an inevitable part of the design process.